2015
DOI: 10.1080/13632752.2015.1032108
|View full text |Cite
|
Sign up to set email alerts
|

Building productive relationships with young people with SEBD in transition: the role of identity

Abstract: This paper reports a study of the experiences of school-leavers with social, emotional and behavioural difficulties (SEBD), which identified supportive relationships as a key element in the young people demonstrating resilience through this transitional period. Almost all the young people involved in the study had access to potential helpers, but few managed to establish productive relationships with them. Analysis of interviews, conducted over a 15 month period with a group of 15 school leavers, their parents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…In this case, the label of SEMH was perceived as indicative of mental illness. Pupils reported greater awareness of, and spoke about, specific diagnostic labels such as ADHD and dyslexia (O'Connor et al, 2011;O'Riordan, 2015;Sheffield & Morgan, 2017;Caslin, 2019). Similar findings are reported by Kelly and Norwich (2004) who found that only 12% of pupils were aware of the term SEN (special educational need); the authors proposed that pupils lack of awareness of such terms could be because they are less likely to hear these terms in everyday interactions.…”
Section: Perceptions Of Semh Labelsupporting
confidence: 65%
See 3 more Smart Citations
“…In this case, the label of SEMH was perceived as indicative of mental illness. Pupils reported greater awareness of, and spoke about, specific diagnostic labels such as ADHD and dyslexia (O'Connor et al, 2011;O'Riordan, 2015;Sheffield & Morgan, 2017;Caslin, 2019). Similar findings are reported by Kelly and Norwich (2004) who found that only 12% of pupils were aware of the term SEN (special educational need); the authors proposed that pupils lack of awareness of such terms could be because they are less likely to hear these terms in everyday interactions.…”
Section: Perceptions Of Semh Labelsupporting
confidence: 65%
“…Of the seven included studies, four studies used the term SEBD (Michael & Frederickson, 2013;O'Riordan, 2015;Mowat, 2015;Caslin, 2019), two studies used BESD (O'Connor et al, 2011;Nind, Boorman & Clarke, 2012) and one study referred to the term SEMH alongside the term BESD (Sheffield and Morgan, 2017), highlighting the evolution of this term in the past 10 years as influenced by educational policy. See Table 2 for a detailed overview of the seven studies included for review and their key study characteristics.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…A move to a new school is a significant transition for any pupil (Evangelou et al 2008) and planned endings of important relationships and careful handover to help establish new key relationships are important aspects of a managed move (Abdelnoor 2007), particularly as pupils who are experiencing difficulties with their social and emotional development and behaviour are likely to find transition and the management of relationships difficult (O'Riordan 2015). This was alluded to by the participants in this study who identified an understanding of the emotions of those involved as a facilitator in creating a sense of belonging for pupils experiencing a managed move.…”
Section: Facilitators For Creating a Sense Of Belonging In Managed Movesmentioning
confidence: 99%